Training on Introduction to Platforms and Utilization of Social Media in Online Business for MSME Actors Students of SMK Alwashliyah 2 Simalungun Regency - Beby Karina Fawzeea Sembiring; Marhayanie Marhayanie; Marhaini Marhaini; Syafrizal Helmi Situmorang; Tetty Yuliaty (Budapest International Research and Critics University, 2021)
Given the blossoming essence of social media marketing, literature does not delve into the complexities and consequences of small and medium-sized enterprises (SMEs). This paper seeks to advance awareness and provide an extensive analysis of the inspiration and efficiency benefits of social media provided by small and medium-sized businesses through a digital economy analysis. The conceptual analysis shows that interactivity, compatibility, and cost-effectiveness are reasons for social media use, ultimately providing advantages. SMEs of Facebook and Twitter profiles are used to analyze the conceptual paradigm suggested. This research reveals that the interdependencies of social media's motives and the consequences of social media use are optimistic but sporadic across small and medium-sized companies. SMEs selling physical goods prefer to use social media on cost-effective motivations, whereas small and medium-sized businesses tend to see interactivity as the main incentive. Furthermore, the study results indicate that Facebook and Twitter in a two-site story generate success gains for small and medium-sized enterprises' users. The study offers future analysis and management priority problems that strongly affect the academic and practice culture. Obviously, despite any bottlenecks in use, SMEs in developing markets tend to reap expanded social media gains through multi-platform marketing activities.